Examining the Effectiveness of Indonesia's Independent and Active Foreign Policy: A Systematic Literature Review and Thematic Synthesis - Yoga Kurniawan; Romy Hermawan (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study examines the effectiveness of Indonesia's foreign policy within the framework of free and active principles through a systematic literature review (SLR) approach. Unlike previous studies that tended to be partial and case-based, this study specifically conducted a thematic synthesis of empirical findings to identify patterns, indicators, and linkages between dimensions of foreign policy effectiveness. Using the PRISMA framework, this study analyzed 22 Scopus indexed scientific articles for the period 2014–2026. The results of the study show that the effectiveness of Indonesia's foreign policy is multidimensional and contextual, which is formed through the interaction between policy orientation, diplomacy instruments, and domestic factors. The main findings reveal that the lack of consistency of effectiveness indicators and institutional fragmentation are the main obstacles in policy implementation. This study contributes through conceptual aggregation that integrates empirical findings into a structured analytical framework, thus offering a clear differentiator compared to previous SLRs that are still descriptive. These findings provide implications for the development of a more systematic and evidence-based foreign policy evaluation.